2030 Agenda and refugees: cornering the rhetoric - Cascante, Kattya (Revista Española de Desarrollo y Cooperación, 2023)
The second semester of 2017 didn’t bring any good news for Spanish development cooperation policy.Even though the 2030 Agenda is still the official policy goal, actual policy is stuck in rhetoric while its institutional structures are dismantled.The same can be said about the government’s refugee policy, with a wide gap between its speeches and its actions.At the same time there is very little interest to depart from short-term national or business interests- The consequence is the continuation of the already characteristic inward-looking policy approach.